Pengembangan Media Pembelajaran Mobile Learning dengan Fitur Gamifikasi pada Materi Kebutuhan dalam Mata Pelajaran IPS - Musthofa, Danis Nurul; Cahyono, Arie Eko; Ulfa, Noviana Mariatul (Jurnal Simki Pedagogia, 2025)
This study aims to develop mobile learning-based educational media, specifically on the topic of needs within the subject of Social Sciences (IPS) at SMP Negeri 8 Jember. By utilizing advancements in information and communication technology, this research adopts the ADDIE development model, which consists of five stages: analysis, design, development, implementation, and evaluation. The results indicate that the developed mobile learning application, named "Social Science Learning Mobile," significantly enhances student engagement and participation in the learning process. Validation by experts shows that this application has a feasibility level of 91%, categorizing it as highly suitable for use. Through the development of this media, it is expected that students will become more motivated, active, and engaged in the learning process, making their learning experience more enjoyable and effective. However, improvements in content and interactive features are still needed to enhance the application's quality. Thus, it is hoped that this application will provide a more engaging and relevant learning experience for students in today's digital era.